(untitled) (Fiep Bulletin - online, 2019)
The investment in technology in sports is directly proportional to performance improvement, in cycling it would not bedifferent, its athletes need to develop very high powers, so equipment, to measure power has a high cost, made the methodrestrictive. This article aims to assess the use of technologies and their efficiency, correlating with the socioeconomic conditionsof youngsters between 15-17 years of both sexes, classified in cycling mode in youth school games. The method applied was adescriptive quantitative research, based on interviews and metadata research, based on the study of public data surveys, namelyIBGE census and other databases. The Olympic Committee divided Brazil for competition in three major regions and for the datacollection it is applied the interview to coaches of all the states, the data were analyzed and compared, therefore we arrived at thefollowing results: The Regions: Southeast and South cycling, the conclusion is that cycling performance is directly linked toequipment investment patterns, such as the potentiometer and the differences between the economic conditions of each regionwhere the south and southeast region has superiority in the school cycling because of the richness seen in GDP and HDI alsodemonstrated with total medals far superior to the North and Northeast.